Economic effects of goodwill accounting practices: systematic amortisation versus impairment test. Issue 2 (3rd April 2021) - Cavero Rubio, José Antonio; Amorós Martínez, Araceli; Collazo Mazón, Antonio
ABSTRACT: Under IFRS, an impairment test is the only method applied to reduce goodwill. However, while the IASB have asked for comments about re-introducing the systematic amortisation method, European directives have already adopted its application. In this dual regulatory framework, we examine whether there are significant differences between the two methods that could affect the comparability of financial statements and their ability to faithfully represent the firm performance. Using a sample of 90 Spanish-listed firms over the period 2004–2011, the panel data technique and t-Student test confirm that under the impairment test, firms are likely to maintain higher amounts of goodwill and not recognise any impairment loss. Consequently, ROA and ROE are higher and leverage is lower. In addition, findings suggest that firms do not correctly implement this method to transmit private information about their economic situation. Results show that the better firm performance is the larger goodwill impairment will be.